El desnudo femenino desde la corriente simbolista como motivo para la representación pictórica contemporánea. - Ludeña Armijos, Karen Elizabeth (2021)
The present research work entitled: The female nude from the symbolist as a motive for contemporary pictoric representation, proposes to analyze the symbolist current from a historical, artistic and aesthetic vision as an important part of the pictorial language for representation and expression, methods were applied for each of the phases of the pictorial research-production emphasizing the theme of the female body as a symbol that adapts to a time, a society and culture. For the development of the pictorial practice, references of artists' works, photographic record of nudes and notes with female models were used, integrating scenarios that form a composition in which the symbolic body-space relationship is generated. All this theoretical structure gives rise to a creative process that results in a pictorial proposal in which the female body is thought critically, reflecting on the character and gestural expression of the body and the implications it has within contemporary society and how it can trigger various interpretations and reactions making it a broad field of study and artistic expression